Cultural lag dalam partisipasi masyarakat pada layanan posyandu - Shabrina Nurul Fauziyyah; Ahmad Ihza Fahlephi; Ayunda Zahra Utami; Athalia Belva; Iman K. Nawireja; Mukhlas Ansori; Rizki Aditya Putra; Ratri Virianita; Nadya Adelaide Vertin (Departemen Pendidikan Sosiologi FISHIPOL UNY, 2026)
This study examines how cultural lag serves as the primary barrier to community participation in preventive health services at Posyandu Melati 6 in Cimanggu 2 Village. Cultural lag emerges when the modernization of posyandu through improved health facilities, digitalized reporting systems, and strengthened cadre capacity develops more rapidly than changes in community values, health knowledge, and behavioral practices. Using a qualitative approach through observations, in-depth interviews, and documentation, the findings show that low health literacy, curative-oriented mindsets, patriarchal norms, and fear of medical procedures are central drivers of this lag between material and nonmaterial cultural elements. To address these gaps, Posyandu Melati 6 implements adaptive strategies including door-to-door outreach, culturally sensitive communication, intensive assistance for high-risk medical cases, and multi-actor collaboration with neighborhood leaders, midwives, and the local health center. This study highlights that improving community participation relies heavily on the posyandu’s institutional capacity to navigate and mitigate the effects of cultural lag while strengthening social legitimacy and organizational resilience.